PENGARUH BESAR MODAL KERJA TERHADAP LABA PERUSAHAAN PADA SUB SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 - Yusuf Siregar (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2020)
This study aims to determine the effect of working capital on profitability in retailer sub sector (93) which is listed on the Indonesia Stock Exchange (IDX). This research is a quantitative research. The population in this study is the Retail Trade Sub-sector company listed on the IDX, in 2018, there were 25 companies. But only 11 companies have data that meet the requirements to be analyzed, because some have moved in the business sector and some have not published their financial statements. The data obtained were processed using t distribution, linearity test, correlation coefficient, and simple linear regression. The results showed that working capital has a positive relationship to company profits, with correlation (r) = 0.420 with a rather low category.